An Antisense Circular RNA Regulates Expression of RuBisCO Small Subunit Genes in Arabidopsis - Zhang, He; Liu, Shuai; Li, Xinyu; Yao, Lijuan; Wu, Hongyang; Baluška, František; Wan, Yinglang (Frontiers in Plant Science, 2021)
From the dataset obtained by high-throughput RNA sequencing, we identified a circular RNA (circRNA) encoded by the sense strand of the exon regions spanning two RuBisCO small subunit genes, RBCS2B and RBCS3B, in Arabidopsis thaliana. We further applied the single specific primer PCR and Sanger sequencing techniques to verify this circRNA and named it ag-circRBCS (antisense-across genic-circular RNA RBCS). Using quantitative RT-PCR (qRT-PCR), we found that ag-circRBCS shares a similar rhythmic expression pattern with other RBCS genes. The expression level of ag-circRBCS is 10 - 40 times lower than the expression levels of RBCS genes in the photosynthetic organs in Arabidopsis, while the Arabidopsis root lacked ag-circRBCS expression. Furthermore, we used the delaminated layered double hydroxide lactate nanosheets (LDH-lactate-NS) to deliver in vitro synthesized ag-circRBCS into Arabidopsis seedlings. Our Results indicate that ag-circRBCS could significantly depress the expression of RBCS. Given that ag-circRBCS was expressed at low concentration in vivo, we suggest that ag-circRBCS may represent a fine-tuning mechanism to regulating the expression of RBCS genes and protein content in Arabidopsis.